Macroprudential regulation and misallocation (2016)
In this paper, we study the macroeconomic effects of  banking capital requirements. We provide a theoretical explanation for why decreasing capital requirements may lead to lower average leverage ratio among banks. This counterintuitive result is an outcome of the general equilibrium effects on interest rates, which affects capital allocation across different types of banks. Additionally, we find that the optimal policy for capital requirements depends on the available equity in the banking sector. Countries with a relatively undeveloped financial sector should have a higher capital requirement. For countries in the middle the optimal policy is a relaxed capital requirement. Finally, countries with a large amount of domestic capital are unaffected by capital requirements.